Massive spectrum in F-theory and the distance conjecture - Keren Chen; Qinjian Lou; Yi-Nan Wang (Journal of High Energy Physics)
Abstract We investigate the massive states in F-theory compactification models, including BPS string junctions stretching between parallel 7-branes and KK modes. We obtain analytical results when there are two colliding bunches of 7-branes with a locally constant axiodilaton profile. In particular, in 8D F-theory setups when the 7-branes collide into a codimension-one (4, 6, 12) singularity, we found an infinite light tower of BPS string junctions, which should match the light KK tower in the dual heterotic description. To exactly match with the results in the distance conjecture, we propose that the definition of 8D Planck mass should receive a large correction. We have also computed parts of KK modes in 8D F-theory in a simplified setup, as well as the BPS string junction spectrum in specific setups of 6D and 4D F-theory.